2017
DOI: 10.4236/ojmc.2017.72002
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study on the Comparative Differences in the Activity of Inhibitors of Human versus Rat Alpha-Glucosidase

Abstract: Differences between the inhibitory activities of specific compounds on analogous enzymes isolated from different animal species are one of the critical issues to evaluate when exploring structure-activity relationships. The activity of acarbose is about ten times stronger in rat than in human, and that of neosalacinol is similar in both species. Binding affinities of acarbose and neosalacinol to four catalytic domains of alpha-glucosidases in human and rat were compared to investigate the cause of activity dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, the N-terminal catalytic domain of rat ntMGAM and that of human ntMGAM (hntMGAM) were reported to share 60% amino acid sequence similarity. 48,49 Thus, it is not surprising that the inhibitory potencies of sulfonium salts such as 1 and 2 against rat maltase were comparable to those against human maltase. 10 In contrast, although the full-length amino acid sequence of yeast a-glucosidase only shares 42% similarity with that of human maltase, the catalytic domain (in the range of 5 Å around the substrate binding site) of yeast a-glucosidase exhibits high similarity (83%) to that of human maltase.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the N-terminal catalytic domain of rat ntMGAM and that of human ntMGAM (hntMGAM) were reported to share 60% amino acid sequence similarity. 48,49 Thus, it is not surprising that the inhibitory potencies of sulfonium salts such as 1 and 2 against rat maltase were comparable to those against human maltase. 10 In contrast, although the full-length amino acid sequence of yeast a-glucosidase only shares 42% similarity with that of human maltase, the catalytic domain (in the range of 5 Å around the substrate binding site) of yeast a-glucosidase exhibits high similarity (83%) to that of human maltase.…”
Section: Resultsmentioning
confidence: 99%
“…Although the inhibitory effects of tea catechins on alpha-glucosidase were validated in rat alpha-glucosidase as undertaken in most studies [ 17 , 18 ], the homology of alpha-glucosidase between rats and humans is only 74% [ 19 ], which affects the inhibitory effect of the compounds [ 20 ]. For this reason, we further investigated the inhibitory activity of GTEs and their catechins on human alpha-glucosidase in differentiated Caco-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that catechins, especially gallate catechins, strongly inhibit alpha-glucosidase activity in S. cerevisiae or a rat model [ 17 , 18 ]. However, the homology of alpha-glucosidase between rats and humans is only 74% [ 19 ], and the difference in the inhibitory effect of alpha-glucosidase by the compound was observed between rats and humans [ 20 ]. For example, acarbose showed lower inhibitory activity in humans than in rats due to the weak interaction of acarbose with the Nt-MGAM domain [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation